CEO incentive plans and corporate liquidation policy1The authors would like to acknowledge the helpful comments of Annup Agrawal, Ravi Anshuman, Betty Strock Bagnani, Jeffrey Cohen, Rebel Cole, Dennis Hanno, Clifford Holderness, Gerald Holtz, Edith Hotchkiss, Kenneth Lehn, Gil Manzon, Morris McInnes, Anil Makhija, Krish Menon, Kevin Murphy (the referee), Laurie Pant, G. William Schwert (the editor), Billy Soo, Robert Taggart, Hassan Tehranian, Sheridan Titman, Paula Varson, Justin Wood, participants in the accounting workshop at Boston College, and John Schatzberg for providing a list of liquidating firms in his sample. An earlier version of this paper, `Executive stock options and ownership, taxes, and corporate liquidation policy,' was presented at the Financial Management Association Meetings in October 1991 and at the Association of Managerial Economists in January 1992.1 - Mehran, Hamid; Nogler, George E.; Schwartz, Kenneth B. (Journal of Financial Economics, 1998)
To investigate CEOs' incentives to liquidate their firms, we examine the effects of insider ownership and compensation in stock options on 30 voluntary liquidation decisions by industrial firms in the period 1975–1986. We find that liquidation decisions are influenced by CEO incentive plans and increase shareholder value. Firms with more outside board members, smaller market-to-book ratios, and attempts by outsiders to gain control are more likely to be liquidated. Although few top executives of liquidating firms subsequently take comparable jobs, at least 41% of CEOs who downsize are made better off by liquidation.